Violence and crime in the family patterns, causes, and consequences - Maxwell, Sheila Royo.; Blair, Sampson Lee. (Bingley, U.K. : Emerald, 2015)
In virtually all societies, crime is an ever-present problem. Although families are often envisioned as a 'safe haven', criminologists and family researchers have found the familial context to be at the core of many forms of crime and violence. Family members often find themselves as victims of crime and violence, often perpetrated by yet another family member. The unique nature of family relationships, such as those between children and parents, sometimes lead to intergenerational patterns of violence within families. Understandably, societies often struggle to address crime and violence within families; as such behaviors are often unreported and even concealed. Even beyond the family, crime and criminal behavior can often directly impact familial relationships, such as with the incarceration of a spouse or parent. This multidisciplinary volume of CPFR will address topics such as: child abuse and neglect, spousal violence, incarceration and parenting, community crime and family well-being, family life and delinquency, intrafamily violence, and policy-related issues pertaining to family violence.
Structural basis of gender violence in cross-regional marriages: tale from Haryana, India / Sonali Mukherjee -- Parental influence and dating violence among students at Nigerian universities / Olufemi Adeniyi Fawole, Ebenezer Bayode Agboola -- Gender, domestic violence, and patterns of conviction: analysis of India's Supreme Court rulings / Preethi Krishnan, Mangala Subramaniam -- Setting the problem of missing children in the Republic of Ireland against contemporary international research perspectives / Michael Rush -- Family of origin and peer influences on intimate partner violence during emerging adulthood / Mallory D. Minter, Monica A. Longmore, Peggy C. Giordano, Wendy D. Manning -- Family violence in Syria / Muaweah Ahmad Alsaleh -- A latent class approach to understanding the intergenerational transmission of violence in emerging adult relationships / Peter M. Rivera, Frank D. Fincham -- Girls' offenders pathways into the Spanish juvenile justice / Rosario Pozo Gordaliza -- "He is still my son": aging and living in the shadow of an abusive adult child with mental disorder / Tova Band-Winterstein, Hila Avieli, Yael Smeloy -- The self and the selfie: cyber-bullying theory and the structure of late modernity / Shahid Alvi, Steven Downing, Carla Cesaroni -- Long-term effects of neglect on violence: are they spurious or indirect? / Joanne Savage, Amanda Murray -- Violent socialization and youth violence across different nations: international variations in familial and contextual factors -- Aimée X. Delaney.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Criminology; Sociology: family & relationships; Family violence